Beer and Racism : How Beer Became White, Why It Matters, and the Movements to Change It - Chapman, Nathaniel; Brunsma, David L. 1970- (Book collections on Project MUSE., 2020)
Beer in the United States has always been bound up with race, racism, and the construction of white institutions and identities. This unique book carves a much-needed critical and interdisciplinary path to examine and understand the racial dynamics in the craft beer industry and the popular consumption of beer.